2020
DOI: 10.5671/ca.44.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Health Adverse Effects of Khat Chewing Among College Students in Jazan Region, Saudi Arabia

Abstract: Khat chewing is a social habit which has stimulatory action due to its cathinone content, but its adverse effects on health are a source of growing concern. The aim of our study is to evaluate the prevalence and health adverse effects of khat chewing among students in Jazan region in the Kingdom of Saudi Arabia (KSA). The study sample included 195 students from Applied Medical Science College, who were randomly selected and were asked through questionnaire and with a signed consent. About 5 ml of venous blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…29 Elbendary et al showed an increase in urea and uric acid but not in creatinine. 30 However, this study demonstrates that the duration of khat chewing and cigarette smoking has a significant effect on uric acid and creatinine levels, implying that khat chewing and smoking have a negative impact on renal function. Al-Habori et al, Brostoff et al, and Masoud et al proposed that uric acid could act as a protective mechanism against the oxidative stress caused by khat.…”
Section: Discussionmentioning
confidence: 54%
“…29 Elbendary et al showed an increase in urea and uric acid but not in creatinine. 30 However, this study demonstrates that the duration of khat chewing and cigarette smoking has a significant effect on uric acid and creatinine levels, implying that khat chewing and smoking have a negative impact on renal function. Al-Habori et al, Brostoff et al, and Masoud et al proposed that uric acid could act as a protective mechanism against the oxidative stress caused by khat.…”
Section: Discussionmentioning
confidence: 54%